Effects of Dubbed Turkish TV Series on Youth’s Adoption of Fashion Trends: A Case study of Lahore and Islamabad - Ahmad, Raza Waqas; Hassan, Ali; Qasim, Lubna (Journal of Peace, Development and Communication, 2021)
Present study explores the rather new phenomenon in Pakistan, dubbed Turkish TV series and their effects in the form of fashion trend on the youth of two major Metropolitans (Islamabad and Lahore) of Pakistan. Literature reveals that dubbed Turkish TV series reached to the Muslim world and significant part of the world. Turkish TV series are raising the image of Turkey as soft power because of their significant cultural cultivation effects on the above said societies. For this, a purposive sample of 400 respondents is taken under the age of 18-23 years males and females equally from Islamabad and Lahore. The findings of the study divulge that significant cultivation effects of dubbed Turkish series observe on the youth. This cultural cultivation is dominant in the form of visual culture and fashion trends. The study also reveals that these significant effects are more persistent on the youth of Islamabad as compare to Lahore. This study has theoretical and corporate implications.